Analis is Faktor-Faktor Yang Me mpe ngaruhi Niat Mengkons ums i Daging Halal(Studi Pada Kons ume n Mus lim di Se marang) - Safitri, Afriana; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2013)
As the increasing of the consumer need of food, especia lly for meat, it is undeniably that the circulation of unhealthy meat is begin to increase, the unhealthy meat itself is meat that not appropriate with the requirments that already allowed toward domestic products or export import product. Furthermore one of the reason that makes this problem increase is the lack of knowledge and ability of consumers to consider the good and right product (meat) properly and safely. This study is aimed to analyze and provide empirical evidence about whether subjective norm and behavioral control influence on religious awareness on halal products and intention to eat halal meat.The population was the moslem peop le of Semarang who ate red meat. The numberof samples are 100 respondents and the sampling method was accidental sampling.This research used a multip le linear regression method with SPSS for windows software.The result showed that subjective norm and behavioral control have positive andsignificant impacts on relig ious awareness on hala l products. Further relig ious awareness on halal products , subjective norm and behavioral control have also positive and significant impacts on intention to eat halal meat. The most dominant v ariable of model 1 is subjective norm, while for model 2, religious awareness on halal products is the highest influence on intention to eat halal meat.